Eighty Five Years of Paediatric Research in the North East of Scotland - A Partnership between Children, Teachers and Researchers - Dorota Chapko; Alison Murray; Graham Devereux; Steve Turner (University of Aberdeen, School of Education, 2017)
There are many common and incurable conditions diagnosed in the elderly, such as dementia and chronic obstructive pulmonary disease (COPD). Understanding the earliest signs of these conditions may lead to early interventions aimed at prevention or cure. A challenge to studying the relationship between childhood factors diseases of the elderly is being able to follow up individuals over the lifecourse. This review describes a series of cohorts of children attending schools in Aberdeen since the mid-1930s have been followed up and where measurements made in childhood have been related to cognitive and respiratory outcomes in later life. Low birth weight combined with premature delivery are associated with low cognition scores during childhood and this persists to the sixth decade. Childhood asthma and non-asthmatic wheezing symptoms were associated with abnormal breathing tests which persists to the seventh decade and is associated with increased risk of COPD. Deprivation in early life is associated with relatively poor cognitive ability in childhood and adulthood but not with childhood asthma. Together, these findings demonstrate that conditions traditionally considered to affect the elderly are potentially detectable in childhood. What remains to be determined is what might be done in early life to prevent or lessen the burden of disease after retirement